Sub-threshold panic attacks and agoraphobic avoidance increase comorbidity of mental disorders: Results from an adult general population sample - Pané-Farré, Christiane A.; Fenske, Kristin; Stender, Jan P.; Meyer, Christian; John, Ulrich; Rumpf, Hans-Jürgen; Hapke, Ulfert; Hamm, Alfons O. (Journal of anxiety disorders, 2013)
•We investigated persons with isolated panic attacks (PA) and panic disorder (PD).•For the first time limited symptom attacks (LSA) were included in analyses.•All panic attack subtypes were associated with frequent comorbidity.•Odds for comorbidity increased from LSA to PA to PD.•The presence of agoraphobia increased comorbidity rates. Full-blown panic attacks are frequently associated with other mental disorders. Most comorbidity analyses did not discriminate between isolated panic attacks vs. panic attacks that occurred in the context of a panic disorder and rarely evaluated the impact of comorbid agoraphobia. Moreover, there are no larger scale epidemiological studies regarding the influence of sub-threshold panic attacks. 4075 German-speaking respondents aged 18–64 were interviewed using the fully structured Munich Composite International Diagnostic Interview. Limited symptom attacks, isolated panic attacks, and panic disorder were associated with other lifetime DSM-IV disorders with monotonically increasing odds and increasing tendency for multiple comorbidities across the three groups. The presence of agoraphobia was associated with more frequent comorbidity in all panic subgroups and also in persons who never experienced panic attacks. The present study suggests that populations with isolated or limited symptom should be carefully attended to in clinical practice, especially if agoraphobia is present.